Laboratory guide "Electric Drive" - Borovikov Y. S. Yuri Sergeevich; Dementiev Yu. N. Yuriy Nikolaevich; Obraztsov K. V. Konstantin Valentinovich; Semenov S. M. Sergey Mikhailovich (Textbooks of Tomsk Polytechnical University)
In the laboratory guide the descriptions of six laboratory works are given, whose topic is research of statics and dynamics of electric DC and AC drives. Laboratory guide is intended for students who study subjects «Electric Drive» and «Automatized electric drive».